New Eastern European Migration to Australia From Czech Republic, Hungary and Ukraine to Sydney and beyond - Oleinikova, Olga. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"This is a timely book about a new wave of migration that has not been well documented until now, from an author with a deep understanding of Eastern Europe and its complex connections to Australia." - Christina Ho, Associate Professor, University of Technology Sydney, Australia "As the son of a Hungarian refugee from the 1950s, the central focus of this book resonates personally, and it is particularly poignant given the Russian invasion of Ukraine and the resulting humanitarian crisis and movement of refugees that has caused. This book is important because it adds to our understanding of the powerful and uniquely individual stories that sit behind migration to Australia and the lasting impact of those cultural traditions and personal histories on the lives that immigrants to Australia build for themselves and their families and on the cultural identities of the emergent diasporas." - Lewis Bizo, Professor and Deputy Dean, University of Technology Sydney, Australia This book identifies and examines new forms and paths of Eastern European migration to Australia since the 2000s, and provides updated trends of contemporary migration movements of Ukrainians, Hungarians and Czechs to Australia. With chapters highlighting the diversities and complexities of these new accelerated waves of Eastern European migration to Asia-Pacific, this book offers novel insights to enrich our understanding of East European mobility in the 21st century. The book will appeal to students, scholars and policymakers in the fields of migration, sociology, political science and international relations. Olga Oleinikova is a Senior Lecturer and Director of the SITADHub (Social Impact Technologies and Democracy Research Hub) in the School of Communication at the University of Technology Sydney, Australia. She is named among Forbes' Top 40 Global Ukrainians, Forbes 30 Under 30 in Asia and is a finalist for the Australia Council of Humanities, Arts and Social Sciences Future Leader Award. She is the author of Life Strategies of Migrants from Crisis Regimes : Achiever or Survivor? (Palgrave Macmillan, 2020).
Keywords: Emigration and immigration; Emigration and immigration -- Social aspects; Ethnology -- Europe; Culture; International relations; Human Migration; Sociology of Migration; Diaspora Studies; European Culture; International Relations